COMPLEX ANALIZ OF THE DANGEROUS CHANGES OF THE GEOLOGICAL SURROUNDING ON AN EXAMPLE OF THE WESTERN DONBASS COAL REGION - Zakchariy, N.; Kurylo, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The problems associated with human pressure on the environment coal region of Ukraine – Western Donbas are examined. Analyzed data digital maps of Dnipropetrovsk region and made zoning areas by degree of damage and suitability for high-quality living population within GIS model. Calculated indicator for the overall risk of dangerous changes in the geological environment and performed score evaluation territory.